Anatomy of Mandibular Vital Structures. Part I: Mandibular Canal and Inferior Alveolar Neurovascular Bundle in Relation with Dental Implantology - Hom-Lay Wang; Gintautas Sabalys; Gintaras Juodzbalys (eJournal of Oral Maxillofacial Research, 2010)
Objectives: It is critical to determine the location and configuration of the mandibular canal and related vital structures during the implant treatment. The purpose of the present study was to review the literature concerning the mandibular canal and inferior alveolar neurovascular bundle anatomical variations related to the implant surgery.Material and Methods: Literature was selected through the search of PubMed, Embase and Cochrane electronic databases. The keywords used for search were mandibular canal, inferior alveolar nerve, and inferior alveolar neurovascular bundle. The search was restricted to English language articles, published from 1973 to November 2009. Additionally, a manual search in the major anatomy, dental implant, prosthetic and periodontal journals and books were performed.Results: In total, 46 literature sources were obtained and morphological aspects and variations of the anatomy related to implant treatment in posterior mandible were presented as two entities: intraosseous mandibular canal and associated inferior alveolar neurovascular bundle.Conclusions: A review of morphological aspects and variations of the anatomy related to mandibular canal and mandibular vital structures are very important especially in implant therapy since inferior alveolar neurovascular bundle exists in different locations and possesses many variations. Individual, gender, age, race, assessing technique used and degree of edentulous alveolar bone atrophy largely influence these variations. It suggests that osteotomies in implant dentistry should not be developed in the posterior mandible until the position of the mandibular canal is established.